2016
DOI: 10.1021/acs.jpclett.6b00803
|View full text |Cite
|
Sign up to set email alerts
|

Is CH3NH3PbI3 Polar?

Abstract: In view of the continued controversy concerning the polar/nonpolar nature of the hybrid perovskite system, CH3NH3PbI3, we report the first investigation of a time-resolved pump-probe measurement of the second harmonic generation efficiency as well as using its more traditional form as a sensitive probe of the absence/presence of the center of inversion in the system both in its excited and ground states, respectively. Our results clearly show that SHG efficiency, if nonzero, is below the limit of detection, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(31 citation statements)
references
References 62 publications
2
27
0
2
Order By: Relevance
“…This can be attributed to the dipoles ordered antiferroelectrically because there has been no evidence of a P – E loop within this low-temperature phase to suggest a ferroelectric state and the crystal structure has been shown in the past to be centrosymmetric. 11 There is clear evidence of a large temperature-dependent contribution from dipoles within the tetragonal phase of MAPbI 3 over the temperature range of 162–300 K in Figure 1b, similar to what is found in the case of MAPbBr 3 . Further, the dielectric constant in MAPbI 3 does not show any discontinuous or even any significant change across the tetragonal to cubic phase transition (similar to ref (20)), indicating a smooth behavior of the dipoles across this phase transition, consistent with our interpretation, as discussed later, of essentially freely rotating dipoles already in the tetragonal phase (see Figure S2 in the Supporting Information).…”
supporting
confidence: 77%
See 2 more Smart Citations
“…This can be attributed to the dipoles ordered antiferroelectrically because there has been no evidence of a P – E loop within this low-temperature phase to suggest a ferroelectric state and the crystal structure has been shown in the past to be centrosymmetric. 11 There is clear evidence of a large temperature-dependent contribution from dipoles within the tetragonal phase of MAPbI 3 over the temperature range of 162–300 K in Figure 1b, similar to what is found in the case of MAPbBr 3 . Further, the dielectric constant in MAPbI 3 does not show any discontinuous or even any significant change across the tetragonal to cubic phase transition (similar to ref (20)), indicating a smooth behavior of the dipoles across this phase transition, consistent with our interpretation, as discussed later, of essentially freely rotating dipoles already in the tetragonal phase (see Figure S2 in the Supporting Information).…”
supporting
confidence: 77%
“…The room-temperature structure of MAPbI 3 is, on average, centrosymmetric, as shown by space- and time-averaged XRD, P – E loop, as well as second harmonic generation (SHG) efficiency measurements. 11 However, this time-averaged description is consistent with many different dynamic behaviors, such as MA + units (i) rotating freely and independently, (ii) rotating in a correlated manner, and (iii) not rotating at all but being frozen in an uncorrelated/random manner giving rise to a glassy state. Thus, it becomes crucial to understand the time scale of rotations of these dipoles and the extent of correlation between different MA + units.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…The ferroelastic orientation state in a material is determined by its unique spontaneous strain tensor, similar to how spontaneous polarization leads to ferroelectricity. According to the available data ( 17 ), MAPbI 3 exists in three crystallographic phases: cubic (italicPitalicmtrue3¯italicm), above 327 K; tetragonal ( I 4/ mcm ), between 327 and 162 K; and orthorhombic ( Pnma ), below 162 K. The cubic-tetragonal transition, which lowers the symmetry from the m 3 m to the 4/ mmm centrosymmetric point group, is a purely ferroelastic transition according to Aizu’s classification (that is, the resulting tetragonal phase can be ferroelastic but not ferroelectric) ( 23 , 24 ). …”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis prompted the fascinating idea that the internal field, due to spontaneous polarization, might be at the origin of the high PCE in OIP solar cells by aiding the separation of photoexcited electron-hole pairs and thus reducing charge recombination ( 16 ). However, solid experimental evidence of ferroelectricity of OIP materials is still lacking, and recent publications ( 17 , 18 ) even question the very polarity of the CH 3 NH 3 PbI 3 (MAPbI 3 ) structure, a necessary requirement for ferroelectricity. In addition, several recent studies conclusively showed that ion migration and the associated charge doping are responsible for the observed hysteretic effects and excluded ferroelectricity as a possible origin ( 19 ).…”
Section: Introductionmentioning
confidence: 99%